The Interplay between Chromatin and Transcription Factor Networks during B Cell Development: Who Pulls the Trigger First? - Choukrallah, Mohamed Amin; Matthias, Patrick (Frontiers in Immunology, 2014)
All mature blood cells derive from hematopoietic stem cells (HSCs) through gradual restriction of their cell fate potential and acquisition of specialized functions. Lineage specification and cell commitment require the establishment of specific transcriptional programs involving the activation of lineage-specific genes and the repression of lineage-inappropriate genes. This process requires the concerted action of transcription factors (TFs) and epigenetic modifying enzymes. Within the hematopoietic system, B lymphopoiesis is one of the most-studied differentiation programs. Loss of function studies allowed the identification of many TFs and epigenetic modifiers required for B cell development. The usage of systematic analytical techniques such as transcriptome determination, genome-wide mapping of TF binding and epigenetic modifications and mass spectrometry analyses, allowed to gain a systemic description of the intricate networks that guide B cell development. However, the precise mechanisms governing the interaction between TFs and chromatin are still unclear. Generally, chromatin structure can be remodeled by some TFs but in turn can also regulate (i.e. prevent or promote) the binding of other TFs. This conundrum leads to the crucial questions of who is on first, when and how. We review here the current knowledge about TF networks and epigenetic regulation during hematopoiesis, with an emphasis on B cell development, and discuss in particular the current models about the interplay between chromatin and transcription factors.